Handbook of research on emerging business models and the new world economic order - Álvarez, José Manuel Sáiz (IGI Global, 2021)
"This book encouraged contributor to forecast future business changes and prospective models, structural or not, for guiding SMEs, multinationals, family firms, entrepreneurs, and NGOs in this pandemic time to survive, thus presenting strategies, economic policies, social, economic, and political trends that could affect organizations to increase their efficiency and labor productivity within he world's business and financial structures."